Stability of the irritable bowel syndrome and subgroups as measured by three diagnostic criteria - a 10-year follow-up study - Olafsdottir, L B; Gudjonsson, H; Jonsdottir, H H; Thjodleifsson, B (Alimentary Pharmacology & Therapeutics, 2010)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field SUMMARY: Background The irritable bowel syndrome (IBS) is a common disorder, but information on its natural history is limited. Aim To study the performance of four IBS criteria in detecting incidence and stability of categories over a 10-year period. Method This study was a population-based postal study. Questionnaire was mailed to the same age- and gender-stratified random sample of the Icelandic population aged 18-75 years in 1996 and again in 2006. IBS was estimated by the Manning criteria, Rome II, Rome III, subgroups and self-report. Results Prevalence of IBS varied according to criteria: Manning showed the highest (32%) and Rome II the lowest (5%). Younger subjects and females were more likely to have IBS. Prevalence was stable over 10 years for all criteria except Rome III. There was a turnover in all IBS subgroups and a strong correlation among IBS, functional dyspepsia and heartburn. Conclusions The prevalence of the IBS remained stable over a 10-year period with a turnover in symptoms. The study suggests that IBS is a cluster of symptoms that float in time between different IBS categories, functional dyspepsia and heartburn. The irritable bowel syndrome in Iceland is very common and indicates a chronic condition, which poses a heavy burden on the health care system.